1999
DOI: 10.1002/hep.510300235
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 modulates intrahepatic resistance in a rat model of noncirrhotic portal hypertension

Abstract: Factors that increase resistance to blood flow through the hepatic sinusoids when portal hypertension occurs in the absence of significant hepatic fibrosis are not completely understood. Experiments were designed to test the hypothesis that endothelin-1 (ET-1) is one of the humoral factors that increases sinusoidal vascular resistance in a bile ductligated noncirrhotic portal hypertensive (BDL) rat. The effect of ET-1 and nitric oxide (NO) on contractility of rings of portal vein taken from BDL rats was tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 39 publications
0
20
0
2
Order By: Relevance
“…16 ET-1-induced constriction of preterminal portal venules causes significant increases in portal pressure in rats, 17 whereas bosentan, a non-receptor-selective antagonist, and BQ123, an ET-1 type A-receptor antagonist, can decrease portal pressure. 9,18 In experimental animals, ET-1 caused increased intrahepatic vascular resistance in the absence of significant fibrosis. 9 Thus, considerable indirect evidence points to ET-1 as a potential mediator of the increased hepatic sinusoidal resistance that results in portal hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 ET-1-induced constriction of preterminal portal venules causes significant increases in portal pressure in rats, 17 whereas bosentan, a non-receptor-selective antagonist, and BQ123, an ET-1 type A-receptor antagonist, can decrease portal pressure. 9,18 In experimental animals, ET-1 caused increased intrahepatic vascular resistance in the absence of significant fibrosis. 9 Thus, considerable indirect evidence points to ET-1 as a potential mediator of the increased hepatic sinusoidal resistance that results in portal hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…9,18 In experimental animals, ET-1 caused increased intrahepatic vascular resistance in the absence of significant fibrosis. 9 Thus, considerable indirect evidence points to ET-1 as a potential mediator of the increased hepatic sinusoidal resistance that results in portal hypertension. The localization of ET-1 in patients with IPH in the present study is consistent with ET-1 affecting hepatic resistance in the absence of hepatic fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that hydrogen peroxide is able to directly activate NF-B, and a variety of antioxidants and antioxidant enzymes, such as catalase, down-regulate TNF-␣-mediated NF-B activation (Schreck et al, 1991;Anderson et al, 1994). TA is a thiono-sulfur-containing compound that is commonly used for inducing fulminant hepatic failure (Bruck et al, 2002) and liver cirrhosis (Kamath et al, 1999) in animal models. During the biotransformation of TA, both flavin-containing monooxygenase (Chieli and Malvaldi, 1984) and cytochrome P450 reduce dioxygen to superoxide anion, which is then catalyzed to produce hydrogen peroxide.…”
Section: Luminescence-based Analysis Of Nf-b Activation 449mentioning
confidence: 99%
“…Indeed, in patients with advanced cirrhosis, flow is the primary determinant of portal pressure. This is largely due to the high levels of circulating endogenous vasodilators that lead to an elevated cardiac output that increases portal blood flow (Q), paradoxically exacerbating portal hypertension (17). It is for this reason that most pharmacological and interventional therapies, such as transjugular intrahepatic portosystemic shunt (TIPS), aim to reduce portal pressure by reducing or redirecting flow to the systemic venous circulation (10,(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%